Philogenetic Analysis of S. Scabiei Var. Hominis, Var. Cuniculi, and Var. Marmoota - Gita Dwi Prasasty; Miftahurrizqiyah; Dalilah; Dwi Handayani; Tia Sabrina; Ahmad Ghiffari; Inda Astri Aryani (HM Publisher, 2021)
Introduction: Based on data from the 2017 Global Burden of Disease, it is known that Indonesia is the country with the highest number of scabies incidences out of 195 countries in the world. In addition to humans, scabies is also an infectious disease in mammals with a prevalence of 300 million infestations every year, even in animals the mortality rate from scabies is very high. Until now, it is still unclear whether there is a cross-infestation between human and animal scabies. Morphologically, S. scabiei between variants cannot be distinguished, while research on genetic variation is still not much done. Therefore, it is necessary to conduct studies to enrich genetic information and phylogenetic analysis. Methods: The samples tested were positive PCR results for ITS 2 and CO 1 genes, each on five amplicons, namely three S. scabiei var. hominis, one var. cuniculi, and one var. marmoota. Phylogenetics were arranged based on the closeness of the base arrangement in variants and geographically available in NCBI. Results: Of the five sample isolates studied, the ITS 2 gene amplicon is located in the 417bp band and the phylogenetic analysis of its sequencing has two branches that are unable to distinguish var. hominis and var. animalia. The CO1 gene has electrophoretic results at 317 bp as well as phylogenetic analysis results that specifically divide branches between var. hominis and var. animalia. Conclusion: S. scabiei var. hominis and var. marmoota, and var. cuniculi are distinct species and are host monospecific.